Autophagy and Senescence in Cancer Therapy. Issue 1 (23rd September 2013) - Gewirtz, David A.
Abstract Autophagy and senescence have multiple and often overlapping and complementary functions in cancer, both in terms of influencing tumor development and in modulating the response to chemotherapy and/or radiation. However, while there is evidence that autophagy induction may accelerate the development of senescence, other studies suggest precisely the opposite, that autophagy inhibition is permissive for senescence. Furthermore, even in those cases where autophagy and senescence appear to occur in tandem, it is clear that the two responses are not interdependent. An additional attribute of senescent cells, both tumor cells and fibroblasts, is the secretion of factors that may influence the growth and/or survival of other cells through paracrine mechanisms. The nature of the secreted factors which mediate these bystander effects remain to be conclusively determined, particularly since senescent fibroblasts and senescent tumor cells appear to exhibit different paracrine functions. Tumor cells tend to secrete factors that promote senescence in "bystander" tumor cells while, conversely, different molecules discharged from tumor‐associated fibroblasts can accelerate tumor growth and metastasis. An understanding of the relationship between autophagy induction and the senescence secretory phenotype in both tumor cells and fibroblasts is likely to be relevant to current clinical efforts to exploit autophagy inhibition as a therapeutic strategy for enhancing the response of malignancies to chemotherapy or radiotherapy. J. Cell. Physiol. 229: 6–9, 2014. © 2013 Wiley Periodicals, Inc.